Hmm - you need to phrase your question a little better. Which of these are you looking for?
x2 - 3x + 2x - 2
= x2 - x - 2
= (x - 2)(x + 1)
x2 - (3x + 2)(x - 2)
= x2 - 3x2 + 6x - 2x + 4
= -2x2 + 4x + 4
= -2(x2 - 2x - 2)
x2 - 3x + 2(x - 2)
= x2 + x - 4
49 - 8 - 6 = 35
-4
ㅗㅓㅕㅗType your answer here...
729
120
That depends what the value of A is.
676
49 - 8 - 6 = 35
-4
Would you mind typing it out for me? I don't quite understand exactly what you are asking. For example, x to the second power minus 4x over x to the second power minus 16 would be... x^2-4x/x^2-16 Do you mind typing it out like that? Because what you wrote makes no sense at all.
That factors to 4t(2t + 1)(5t - 6)
That factors to 3(m - 4n)(6m - n)
which of the following is a factor of x2 - 5x - 6
1.39 times 10 to the 2nd power is 139
35x2-44x-7 = (7x+1)(5x-7) when factored
7(x - 2)(x + 2)
4C2 * (-2CD2) = -8C3D2